کاریگەری داعش لەسەر گۆڕینی نەخشەی سایکس- پیکۆ و پرسی کورد - سادق, بارزان جه‌وهه‌ر (Sulaimani Journal for Humanities, 2018)
Abstract After a century of persist map of Sykes- Picot agreement, today Islamic State (ISIL) has distributed these borders and reformulated the geo-policy of the region based on its logical and its original owners. Al- Qaeda Organization, Invasion of Iraq, Arab Spring and were some clashed accident and had effect on the changing situation of the map's borders. After these coincidences, regional countries lands have divided, and never can be re-unite by using power. It is national geography, religion and culture that redesign the boarders, not powerful states or interests. Kurds were the first victims of that division, while Sever Treaty in 1920 gave Kurds a big hope, but three years after Luzon Treaty, vanished all the Kurd's dreams. It is almost a half century; that Kurds are trying to re-correct that historical mistake. Its Victims cannot be counted for redesign and surviving from invasion. Even ISIL's occupy caused a big disaster for Kurd, but as said "there is an interest in every war" after ISIL, Kurdish question entered a new stage that now they are treated as an independent state in two parts of Kurdistan and they refused these borders. This research attempts to show some arguments to recognize the assumption that focused on distributing of Sykes- Picot Agreement is in Kurd's benefit. There is a theoretical framework in the first chapter about ISIS and Iraq and Syria maps in Sykes-Picot agreement. Then, the effect of ISIL on dividing Iraq and Syria. In this chapter, we explained those conditions that made the agreement abolished, such as invasion and leaving Iraq by US, Arab Spring in Iraq and Syria in the same year and dividing these two countries due to ISIL's conquers. At the end, we will try to show where the Kurdish question is going after those changes and weather that new division is in Kurds interests or not.